2013
DOI: 10.1155/2013/928315
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases: Inflammatory Regulators of Cell Behaviors in Vascular Formation and Remodeling

Abstract: Abnormal angiogenesis and vascular remodeling contribute to pathogenesis of a number of disorders such as tumor, arthritis, atherosclerosis, restenosis, hypertension, and neurodegeneration. During angiogenesis and vascular remodeling, behaviors of stem/progenitor cells, endothelial cells (ECs), and vascular smooth muscle cells (VSMCs) and its interaction with extracellular matrix (ECM) play a critical role in the processes. Matrix metalloproteinases (MMPs), well-known inflammatory mediators are a family of zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
325
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(347 citation statements)
references
References 139 publications
8
325
0
14
Order By: Relevance
“…Therefore, EPC behavior is greatly regulated by chemical and physical properties of their surrounding ECM. 55 Hanjaya-Putra et al have demonstrated that soft matrix reduces the MMP production by EPCs while increasing cell elongation and extending intracellular vacuoles to open lumen compartments through a signaling pathway involving the activation of the Rho GTPase Cdc42. 56 Not surprisingly, when normal tissue homeostasis becomes imbalanced, as can occur during tissue injury, tissue function can become impaired.…”
Section: Cellular Response To Ecm Stiffness During Tissue Homeostasismentioning
confidence: 99%
“…Therefore, EPC behavior is greatly regulated by chemical and physical properties of their surrounding ECM. 55 Hanjaya-Putra et al have demonstrated that soft matrix reduces the MMP production by EPCs while increasing cell elongation and extending intracellular vacuoles to open lumen compartments through a signaling pathway involving the activation of the Rho GTPase Cdc42. 56 Not surprisingly, when normal tissue homeostasis becomes imbalanced, as can occur during tissue injury, tissue function can become impaired.…”
Section: Cellular Response To Ecm Stiffness During Tissue Homeostasismentioning
confidence: 99%
“…sponsible for tadpole tail resorption [10][11][12]. Since then, the MMP family has grown to include at least 23 members in humans and 24 in mice.…”
mentioning
confidence: 99%
“…Since then, the MMP family has grown to include at least 23 members in humans and 24 in mice. Some of them are not yet fully understood [10,13]. Matrix metalloproteinases are considered members of the multigene metzincin family, which also includes transmembrane and secreted proteins called a disintegrin and metalloproteinases (ADAMs), a disintegrin and metalloproteinase with thrombospondin mofits (ADAMTSs), bone morphogenic protein 1/tolloid-like metalloproteinase (BMPI/ /TLLs) and meprins [14,15].…”
mentioning
confidence: 99%
“…ECM, upon its degradation by MMPs, releases FGFs that are stored or trapped within by MMPs. Otherwise, FGFs may associate with a carrier protein that delivers these FGFs to their respective receptors and in turn activate them [86].…”
Section: Fgf and Fgfrs: Roles In Cancermentioning
confidence: 99%